PENGARUH PENGALAMAN KERJA, TEAMWORK DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA DINO PARK, JATIM PARK 3 (PT. MAJU BATU BERSAMA) DI KOTA BATU - Shintia Putri Salsabilla (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Jatim Park 3 is a company operating in the tourism sector. The condition of employees in Jatim Park 3 in the Dino Park section has problems in terms of inadequate work experience so that there are many errors in work, teamwork is not implemented so that the work results are less effective and lack of job training for new employees means that the performance expected by the company is not achieved. The research objective to be achieved in accordance with the problem formulation described above is to determine, analyze and answer the role of Work Experience, Teamwork and Job Training partially and simultaneously on Employee Performance at Dino Park, Jatim Park 3 (PT. Maju Batu Bersama). This research uses primary data. With a population of 80 employees, the number of samples used is a saturated sample. And the testing in this research uses quantitative methods. The analytical tool used is the SPSS version 26 program. The results of the validity test for all indicators are valid (because the Corrected Item-Total Correlation value is greater than rtable), while the reliability test for all indicators is reliable (because the Cronbach's Alpha coefficient value is > 0.60). For the classical assumption test results, all results meet the criteria, namely 1) normality test on the Asymp value. Sig. (2-tailed) >0.05, 2) the regression model is free from multicollinearity, 3) heteroscedasticity does not occur. Multiple linear results show that all variables have a positive and significant effect. The results of hypothesis testing all independent variables have a positive and significant effect on employee performance and simultaneously have a significant effect on employee performance. Analysis of the coefficient of determination (R²) shows that the Adjusted R square is 0.931/ 93.1% of the influence of the variables work experience (X1), teamwork (X2) and job training (X3). The remaining 6.9% is influenced by other variables.